MUE705 : Curriculum design in music education / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
This course exposes students to the various terminologies and practices associated with curriculum design. It leads students from the fundamentals of curriculum construct to the creation of quality curriculum products. Students learn about the historical development of curriculum models and compare its characteristics. They review and critique contemporary national and international music curriculum practices. Students learn to design curriculum premised on outcome-based education and student-centred learning as well as the design of music assessment rubrics and constructive alignment of course and programme content.